The Effect of Financial Performance and Firm Size on Stock Prices, with Dividend Policy as a Moderating Variable - A. Rendy Sandra Mamola; Dini Wahjoe Hapsari (PT Mattawang Mediatama Solution, 2026)
This study aims to analyze the impact of financial performance and firm size on stock prices, with dividend policy as a moderating variable, among conventional banking firms listed on the Indonesia Stock Exchange (IDX) during the 2018–2024 period. Employing a quantitative research design, the study utilizes secondary data collected from the annual reports and financial statements of banking firms. The sample was determined through purposive sampling, resulting in 77 firm-year observations. Panel data regression was applied to test the proposed relationships. The results indicate that ROE has a positive and significant effect on stock prices, suggesting that higher corporate profitability leads to greater investor confidence and higher market value. Conversely, firm size does not have a significant effect on stock prices, suggesting that firm scale alone is insufficient to influence investors’ investment decisions. Additionally, the DPR was found to moderate the effect of ROE on stock prices but failed to moderate the effect of firm size on stock prices. These findings suggest that banking sector investors place greater emphasis on a company’s ability to generate profits and the consistency of its dividend payouts compared to company size when assessing investment prospects. The study’s results support Signaling Theory, which asserts that profitability and dividend policy serve as relevant signals in stock price formation.